PENERAPAN METODE TILAWATI DALAM PEMBELAJARAN MEMBACA AL-QUR’AN SISWA DI SMP AL MUSLIM BEKASI - Sandy -; Irham - (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2021)
This study seeks to determine the Tilawati method in learning to read the Qur’an of studentsat SMP Al Muslim Bekasi. Then besides trying to explore the reasons for using the Tilawati methodin learning to read the Koran for students at SMP Al Muslim Bekasi, then trying to explore theapplication of the Tilawati method in learning to read Al-Qur’an students at SMP Al Muslim Bekasias well as looking for advantages and disadvantages. his weakness. The research method used isa naturalistic qualitative method, namely research that is based on a phenomenological view andseeks to understand the meaning of events and their relationships to the object of research. This studyformulates how the application of the Tilawati method in learning to read the Qur’an of students usedat SMP Al Muslim Bekasi? Then why was the Tilawati method chosen at SMP Al Muslim Bekasi?Furthermore, what are the strengths and weaknesses in applying the Tilawati method in learning toread the Koran for students at SMP Al Muslim Bekasi? This study found at least 3 findings, namely:first, the Tilawati method is a method that uses a classical approach, reads and listens in a balancedway, and uses a rost tone, and contains the knowledge of recitation to the level of musykilat and gharib(the recitation is complete). Second, the reason why the Tilawati method is used at SMP Al MuslimBekasi, is because learning to read the Qur’an using the Tilawati method is easy to understand, and theprogram can be added up to tarjim and tahfidz and student level promotion exams can be carried outaccording to the school schedule. Third, the application of the tilawati method in schools, (1) studentsare arranged to form a letter “U”, (2) the teacher leads the opening prayer, (3) the teacher leads byreading classical, (4) the teacher leads by reading listen, (5 ) student deposit (6) closing prayer. Thenthe advantages and disadvantages of the Tilawati method, As for the advantages, the tilawati methoduses a classical approach and reads and listens in a balanced way and has a characteristic rost tone.Furthermore, the weakness of the Tilawati method is the limited time, the explanation of makharijulletters is less detailed or detailed, and less ghiroh.Finally, this study concludes that the applicationof the tilawati method in learning to read the Qur’an of students at SMP Al Muslim Bekasi betweenpractice and instructions is appropriate, then if it is associated with the science of recitation it hasreached musykilat and gharib (completed).